Proteínas de reparo (PMS2 E MSH6) e ERG e seu papel no câncer de próstata em prostatectomias radicais: correlação clínico patológica - Feitosa, Priscilla Mariana Freitas Aguiar (2023)
Prostate cancer is the most diagnosed male malignancy in worldwide. Recent work suggests that the rate of microsatellite instability (MSI) in primary prostate tumors is <4% and suggests that patients with higher ERG expression intensity were significantly more likely to develop biochemical relapse, metastasis, and prostate cancer-specific mortality. The objective was tocorrelate gene expression of PMS2, MSH6 and ERG with classic pathological clinical prognostic markers. For this, a retrospective cohort was constituted, and tissue microarray immunohistochemistry (TMA) reactions were performed on samples taken from non-neoplastic and neoplastic tissues, characterizing, evaluating, relating, and comparing the expression of PMS2, MSH6 and ERG markers. It was a total of 680 samples from adenocarcinoma patients undergoing radical prostatectomy, after following exclusion criteria a 635 samples remained. Age over 60 years showed odds ratios in relation to the absence of PMS2 and MSH6 marking equal to 4.31 and 1.58, respectively. There was no significant difference in relation to marked MSH6, PMS2 and ERG and PSA levels above 10 ng/ml. Individuals who did not have positive MSH6 labeling have an odds ratio of 6.40 for biochemical recurrence. There is no statistically significant difference between the groups that marked and did not mark MSH2 with respect to biochemical recurrence. The group who did not mark MSH6 and/or PMS2 had higher Gleason scores and there is no statistically significant difference between the Gleason score values (pooled) between individuals who marked and those who did not mark ERG. The group of patients who did not score MSH6 showed worse pictures regarding staging.There is a higher frequency of metastasis among patients without MSH6 marking. There is no statistically significant difference regarding the presence of ERG or absence of PMS2 and presence of metastasis. MSH6 and PMS2 markers were not significantly associated with many of the evolutionary outcomes evaluated, a fact that we can explain due to the fact that our patients belonged to the low-risk group. Of the ERG positive patients (190/635), two with weak and focal marking, seven with moderate marking and two with marked marking showed metastasis. In conclusion, age over 60 years was not statistically significant in relation to the presence of ERG and absence of PMS2 and MSH6 marking. Negative MSH6 labeling and/or positive ERG labeling shows a relationship with biochemical recurrence. Gene expression of PMS2, MSH6 and ERG had no association with PSA levels above 10 ng/ml. Gleason score values were higher in the group that did not tag MSH6 and/or PMS2 and there was no association with the presence or absence of ERG tagging. There is evidence that there is a difference in staging between the groups that did and did not mark PMS2 and ERG and that there is a higher frequency of metastasis among patients without MSH6 marking. In addition, patients with moderate to strong ERG labeling have higher staging compared to the others. Further studies should be conducted to corroborate the elements cited and future work can use these data for associations with other clinical outcomes.